2023
DOI: 10.3390/su15043038
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fertilizers and Pesticides in Wheat Production in the Main European Countries

Abstract: The aspects highlighted in this paper refer to the application of fertilizers and plant protection products to the wheat crop, and their impact on total production, competitiveness in export markets, price optimization as a result of increased harvest quality, and not least row, ensuring farmers’ incomes. The present analysis concerned the areas cultivated with wheat, and the productions achieved in relation to the quantities of fertilizers and protection products used in wheat cultivation, in Romania, Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Additionally, contaminants like met-als and hydrocarbons originate from vehicle emissions. Agricultural pollution primarily results from the runoff of fertilizers [30] and pesticides [31] into water streams, often containing nitrogen, phosphorus, or sulfur, which subsequently leads to soil contamination and groundwater pollution [32]. However, the most significant and dangerous source of pollution comes from industrial activities, given the multitude of materials and substances present in industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, contaminants like met-als and hydrocarbons originate from vehicle emissions. Agricultural pollution primarily results from the runoff of fertilizers [30] and pesticides [31] into water streams, often containing nitrogen, phosphorus, or sulfur, which subsequently leads to soil contamination and groundwater pollution [32]. However, the most significant and dangerous source of pollution comes from industrial activities, given the multitude of materials and substances present in industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…We know that the yield of wheat is most affected by the application of adequate fertilizers and pesticides, which is also the case with other crops. Some authors [6] investigated the factors that most affect wheat yields in European countries and observed that the applied technology in production, the type and number of treatments with fertilizers and pesticides, etc., are equally important. They found an insignificant correlation between applied nitrogen, phosphorus, potassium, and average wheat production in countries like Spain and Italy, while in Romania and Hungary this correlation is very strong.…”
Section: Introductionmentioning
confidence: 99%
“…Yield at harvest is a genetically controlled trait [13,14]. However, environmental factors and farming practices often lead to variations in yield [15][16][17]. Yield variability in wheat is influenced by several agronomic factors, with nitrogen management being crucial among them.…”
Section: Introductionmentioning
confidence: 99%